1876 Colo. Sess. Laws 304, § 154 - (:unkn) unknown (General Publisher, 1876)
Prohibited the carrying with intent to assault another any pistol, gun, knife, dirk, bludgeon, or other offensive weapon.
--
Keywords: CARRY - INTENT TO COMMIT CRIME